2005
DOI: 10.1089/hum.2005.16.1194
|View full text |Cite
|
Sign up to set email alerts
|

Electrophoretic Component of Electric Pulses Determines the Efficacy of In Vivo DNA Electrotransfer

Abstract: Efficient DNA electrotransfer can be achieved with combinations of short high-voltage (HV) and long lowvoltage (LV) pulses that cover two effects of the pulses, namely, target cell electropermeabilization and DNA electrophoresis within the tissue. Because HV and LV can be delivered with a lag up to 3000 sec between them, we considered that it was possible to analyze separately the respective importance of the two types of effects of the electric fields on DNA electrotransfer efficiency. The tibialis cranialis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 126 publications
(37 citation statements)
references
References 35 publications
1
36
0
Order By: Relevance
“…Prior studies have shown that the combination of a short-duration, high-field-strength first pulse, together with a longer-duration, lowerfield-strength second pulse (denoted by 'first pulse' and 'second pulse', respectively) can increase electroporation efficiency and preserve cell viability, especially when delivering larger molecules (MW N 4 kDa [47]) or DNA [33,34,37,39,42,[57][58][59][60][61][62][63][64][65][66]. Pulsing parameters have been well studied, including the strength of the first pulse [33,37,58], the strength and duration of the second pulse [34,39,[57][58][59], and the delay between pulses [34,42,57,58,66,67].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies have shown that the combination of a short-duration, high-field-strength first pulse, together with a longer-duration, lowerfield-strength second pulse (denoted by 'first pulse' and 'second pulse', respectively) can increase electroporation efficiency and preserve cell viability, especially when delivering larger molecules (MW N 4 kDa [47]) or DNA [33,34,37,39,42,[57][58][59][60][61][62][63][64][65][66]. Pulsing parameters have been well studied, including the strength of the first pulse [33,37,58], the strength and duration of the second pulse [34,39,[57][58][59], and the delay between pulses [34,42,57,58,66,67].…”
Section: Introductionmentioning
confidence: 99%
“…Pulsing parameters have been well studied, including the strength of the first pulse [33,37,58], the strength and duration of the second pulse [34,39,[57][58][59], and the delay between pulses [34,42,57,58,66,67]. The two-pulse protocol has been reported to significantly increase delivery efficiency both in vitro in cell suspensions as well as in vivo in a variety of tissues [33,57] as compared to a single electroporation pulse.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to viral vector transfer, the use of electric pulses for gene delivery represents a safer method, which is not hampered by concerns of immunogenicity and pathogenicity13. Different protocols where designed for in vitro and in vivo applications, either employing short hundreds-of-microsecond pulses4, long millisecond pulses7814 or combining high-voltage (10–1000 μs) and low-voltage (10–400 ms) pulses121516171819. We have recently shown in vitro that2021 longer electric pulses are optimal for high transfection efficiency but reduce viability, while shorter pulses enable moderate transfection efficiency and preserve viability.…”
mentioning
confidence: 99%
“…Nowadays, it has been commonly used for introducing genetic material to cells [27], and for delivering drugs across the cell membrane. However, there are also a lot of factors which can influence the transfection efficiency of this method, such as electric pulses [30], reactive oxygen species [31], inhibitors of endocytosis [32], and so forth. In this study, we confirmed successful transfer of the plasmid encoding pCMV-HA- pprI and found expression in mice 1 day after radiation, but not subsequently.…”
Section: Discussionmentioning
confidence: 99%